Projections of precipitation and temperature changes in the Neelam River Basin, western Himalaya: a CMIP6-based assessment under shared socioeconomic pathways - Iqbal, W.; Cheema, Muhammad Jehanzeb Masud; Anjum, M. N.; Amin, M.; Hussain, S. (Springer, 2025)
This study assessed the past and future precipitation and temperature changes in the Neelam River basin, which is located in the western Himalayas. The projections of five General Circulation Models (GCMs) from the Coupled Model Intercomparison Project Phase 6 (CMIP6) were used to analyze the future climate change in the basin. The delta change method was used for the bias correction of the GCMs. The anticipated changes in temperature and precipitation for the near future (2021–2050) were computed under three Shared Socioeconomic Pathways (SSPs; SSP2-4.5, SSP3-7.0, and SSP5-8.5) relative to the baseline period (1985‒2014). The Modified Mann-Kendall (MMK) test was used to assess the significance of temperature and precipitation trends, and the Theil-Sen (TS) slope estimator was used to examine the slope of the trends. According to projections made under all SSPs, the average annual precipitation may decrease in the future. The possible reduction of precipitation varies between − 4.56% (under SSP2-4.5) and − 4.77% (under SSP5-8.5). All SSPs showed a significant decrease in future spring precipitation, with rates of -0.49 mm/year, -6.21 mm/year, and − 4.74 mm/year under SSP2-4.5, SSP3-7.0, and SSP5-8.5, respectively. Under all SSPs, both the minimum temperature (TMin) and maximum temperature (TMax) exhibited significant increases, with the most notable increase in annual TMin under SSP5-8.5, at a rate of 0.07 °C/year. The projected changes in precipitation and temperature may result in more frequent and severe droughts, which would negatively affect the ecosystem, crop production, and hydropower generation in Pakistan. This study provides critical insights for policymakers to devise targeted adaptation and mitigation measures for the Neelam River basin to address the impacts of climate change.